Source attribution of human echinococcosis: A systematic review and meta-analysis. - Paul R Torgerson; Lucy J Robertson; Heidi L Enemark; Junwei Foehr; Joke W B van der Giessen; Christian M O Kapel; Ivana Klun; Chiara Trevisan (Public Library of Science (PLoS), 2020)
Background A substantial proportion of echinococcosis transmission to humans via contamination of food has been assumed. However, the relative importance of food as a transmission vehicle has previously been estimated through expert opinion rather than empirical data. Objective To find and evaluate empirical data that could be used to estimate the source attribution of echinococcosis, in particular the proportion that is transmitted through contaminated food. Methods A systematic review was undertaken to identify reports on the risk factors for human cystic (CE) and alveolar (AE) echinococcosis. Data bases searched included PubMed, Scopus, Web of Knowledge, Cab Direct, Science Direct, Google Scholar, eLIBRARY.RU, CyberLeninka, CNKI and VIP. Search terms included Echinococc*, hydatid, epidemiology, logistic regression, risk factors, odds ratio, relative risk, risk factors. Reports, including grey literature where available, that had suitable data were selected and data were extracted. The main pathways of transmission were hypothesised to be contact with the definitive host, contaminated water, contaminated food and contaminated environment (other than food). For each study the attributable fraction for these potential sources of infection was calculated from the data presented. A meta-analysis was then undertaken to obtain pooled estimates for the relative contribution of these transmission pathways. Results Data from 28 cross-sectional studies and 14 case-control studies were extracted. There was strong evidence for transmission by direct contact with dogs for both CE and AE. The estimated attributable fractions were 26.1% (CI 13.8%-39.6%) and 34.4% (CI 20.7% -48.2%) respectively. Transmission through contaminated water was estimated to be responsible for approximately 29.4% (CI 12.1%-51.7%) for CE and 24.8% (CI 10.6% to 42.6%) for AE. Contaminated food may be responsible for approximately 23.4% of CE cases (CI 2.1%-47.3%). Globally, there was insufficient evidence to conclude AE can be transmitted by food, although case control studies from low human incidence areas suggested that possibly 32.5% (CI 10.0%-53.2%) could be transmitted by food. There was also insufficient evidence that direct contact with foxes was a significant source of human disease. There were no suitable studies with a risk of environmental contact reported, but the residual attributable fraction thatwould likely include this pathway was approximately 21.1% for CE and 11.1% for AE. Conclusions The results support the hypothesis that dog contact and drinking contaminated water are major pathways of transmission of both CE and AE. For contaminated food, the results are less consistent, but suggest that it is an important transmission pathway and provide better evidence than expert elicitations as previously used.